Ciliary body toxicity of cyclosporin A and octreotide acetate in rabbit eyes - Akyol, N; Demir, T; Çobanoglu, B; Ulas, F (Springer-Verlag, 2003)
Purpose. To compare the toxicities of cyclosporin A, octreotide acetate, mitomycin C and 5-fluorouracil to the ciliary body. Method. We applied sponges soaked in these compounds to the open scleras of rabbit eyes. Histopathological specimens were obtained from the operation site and at 180degrees from it on the 14th day after surgery. Results. Mean ciliary epithelial thickness in the study groups was as follows: 12.29+/-2.69 mum in group 1 (mitomycin C), 13.85+/-4.56 mum in group 2 (5-fluorouracil), 17.71+/-3.09 mum in group 3 (cyclosporin A), 11.64+/-2.92 mum in group 4 (octreotide acetate), 11.92+/-2.89 mum in group 5 (topically applied octreotide acetate) and 21.85+/-4.29 mum in group 6 (control). The ciliary epithelial thickness in groups 1, 2, 4 and 5 was statistically different from that in the control group. Intracellular vacuolisation and degenerative changes of the non-pigmented epithelium, and pigment loss of the pigmented epithelium, were found mostly in group 1 and moderately in group 2 and 3. Conclusion. Octreotide acetate and cyclosporin A are less toxic alternatives to mitomycin C and 5-fluorouracil in glaucoma filtration surgery.
Keywords: Rats; Trabeculectomy; Fistulas